واقع التفكير الإبداعي وعلاقته بالبيئة التعليمية من وجهة نظر معلمي المرحلة الابتدائية بمدينة زليتن (Journal of Humanitarian and Applied Sciences, 2023)
The study aims to reveal the reality of creative thinking and its relationship to the educational environment from the point of view of primary school teachers. The study used the descriptive analytical method. The study sample included 393 male and female teachers, and a questionnaire tool prepared by the researcher was applied to the sample, consisting of (24) items. The study concluded that To the following results:1- The reality of creative thinking in the educational environment from the point of view of primary school teachers was at a high level.2- There is a strong and positive relationship between creative thinking and the school environment from the point of view of primary school teachers.3- There is a strong and positive relationship between motivation-based education and the school environment from the point of view of primary school teachers.
Keywords: creative thinking; educational environment; primary stage